Pathology of the Model of Wind Turbine Manufacturing Technology Transfer Iran - Rahmani, Sajjad; Fazli, Mohammad Hassan (Ciência e Natura, 2015)
Attention to Renewable energy resources, first, because of the increasing environmental pollution and climate change, and the second due to reduce supplies of fossil fuels, is one of the policy priorities in many countries, especially developed countries has become. because of a broad range of environmental damage and international commitments, developing countries have been obliged to enter into this field. attention to the gap between developed and developing countries in the field of renewable energy technologies, technology's transfer the first and most effective way for developing countries in this field. Iran also is no exception and takes a step in this direction. given the obstacles and challenges that there are in developing countries for technology's transfer, this paper a review of a project comes in technology's transfer in the field of wind turbines. the main reasons for the success of the project are indentified and improved model is proposed for future project.